PEMANFAATAN WEBSITE LITERACY CLOUD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Rosyidah, Siti; Ahmad Syahid, Aah; Nur Aeni, Ani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The literacy cloud website can be utilized by students and teachers in assisting the learning process. This study aims to determine the utilization of the literacy cloud website as a learning media in grade V elementary schools. This research uses a qualitative method with a case study design. The data collection techniques taken were observation, interviews, open-ended questionnaires and documentation. The subjects in this research are teachers and all students of class V B at SD Negeri Sindang IV. The results of the research on the utilization of the literacy cloud website as a learning media in grade V elementary schools show very good results. The results refer to teachers who are able to use the literacy cloud website to integrate it into Pancasila education subjects. The teacher revealed that he had experienced obstacles in integrating the literacy cloud website with Pancasila education subjects, but in the process the teacher was able to overcome these obstacles. Marked by all students who gave positive responses to the use of literacy cloud in learning. Students feel helped in interpreting their understanding, especially in Pancasila education subjects. Students feel a new, comfortable and fun nuance when learning. This literacy cloud website is highly recommended for various groups such as children, parents and teachers to introduce to their students either as learning media or alternative reading. ABSTRAK Website literacy cloud dapat dimanfaatkan oleh siswa maupun guru dalam membantu proses pembelajaran. Penelitian ini bertujuan untuk mengetahui pemanfaatan website literacy cloud sebagai media pembelajaran di SD kelas V. Penelitian ini menggunakan metode kualitatif dengan desain studi kasus. Teknik pengumpulan data yang diambil yaitu observasi, wawancara, angket terbuka dan dokumentasi. Subjek dalam penelitian ini adalah guru dan seluruh siswa kelas V B di SD Negeri Sindang IV. Hasil penelitian pemanfaatan website literacy cloud sebagai media pembelajaran di SD kelas V menunjukkan hasil yang sangat baik. Hasil merujuk pada guru yang mampu menggunakan website literacy cloud hingga mengintegrasikannya pada mata pelajaran pendidikan pancasila. Guru mengungkapkan sempat mengalami kendala dalam memadukan website literacy cloud dengan mata pelajaran pendidikan pancasila, namun pada prosesnya guru mampu mengatasi kendala tersebut. Ditandai dengan seluruh siswa yang memberikan tanggapan positif terhadap pemanfaatan literacy cloud dalam pembelajaran. Siswa merasa terbantu dalam menginterpretasikan pemahaman mereka, khususnya pada mata pelajaran pendidikan pancasila. Siswa merasakan nuansa yang baru, nyaman dan menyenangkan ketika belajar. Website literacy cloud ini sangat direkomendasikan untuk berbagai kalangan seperti anak-anak, orang tua maupun guru untuk diperkenalkan kepada siswanya baik sebagai media pembelajaran ataupun alternatif bacaan.